Sustainable Epoxy Biocomposites Reinforced With Tenebrio molitor Biofiller: A Comprehensive Study on Thermal, Mechanical, and Dielectric Properties - Ozgen, Inanc; Aydogmus, Ercan; Oner, Ilyas; Karagoz, Mustafa Hamdi; Arslanoglu, Hasan (Wiley, 2025)
Obtaining biological material by drying and grinding Tenebrio molitor insects is original research in the field of innovative materials science. This study investigates the impact of T. molitor biofiller on the thermal, mechanical, and dielectric properties of epoxy-based biocomposites. The results revealed that increasing the content of the biofiller (from 0 to 4 wt.%) significantly reduced the bulk density (from 1134 to 1096 kg/m3), the Shore D hardness (from 77.6 to 73.1) and the thermal conductivity (from 0.112 to 0.090 W/mK), while enhancing the thermal insulation properties. A non-linear regression model confirmed the progressive reduction in density, with an optimal biofiller ratio of 2 wt.% minimizing trade-offs in thermal stability (activation energy: 178.37 kJ/mol). Dielectric constant measurements (4.09-3.78) showed improved insulating properties. Scanning electron microscopy (SEM) and other microscopic analyses confirmed homogeneous filler distribution and preserved structural integrity at optimal loadings. These findings highlight the potential of the biofiller-reinforced composites for use in lightweight, sustainable applications in the construction, electronics, and automotive industries, in line with the goal of innovating eco-friendly materials.
Keywords: bulk density; epoxy biocomposites; shore D hardness; Tenebrio molitor; thermal conductivity; thermal stability